Sequential mediation of early temperament and eating behaviors in the pathways from feeding practices to childhood overweight and obesity - Zhang, Xiaoning; Zhou, Qiong; Vivor, Nathaniel Kossi; Liu, Wei; Cao, Junli; Wang, Sheng (Frontiers in Public Health, 2023)
Previous research suggests a potential association between childhood temperament, feeding practices, childhood eating behaviors and overweight/obesity (OW/OB).No study has specifically examined the impact of feeding practices on childhood OW/OB, while considering the mediating roles of eating behaviors and temperament in children aged 6-23 months.This is the first study conducted in low-and middle-income countries (LMICs) to establish the pathways from maternal feeding practices to childhood OW/OB, and explored the mediators of childhood temperament and eating behaviors using a structural equation modeling (SEM) approach.This study provides significant evidence regarding the impact of maternal feeding practices on childhood OW/OB. The findings have practical implications for guiding intervention strategies to prevent childhood OW/OB through the sequential mediation of childhood temperament and eating behaviors.This study provides valuable insights that can assist governments agencies, policymakers, and healthcare workers in designing and implementing optimal clinical intervention programs targeting maternal feeding practices through mediators of childhood eating behaviors and temperament to prevent childhood OW/OB.